Pendampingan Pengembangan Pembelajaran Berorientasi HOT’s (Higher Order Thinking Skills) bagi Guru MADIN SMP Islam Bustanul Hikmah Lamongan - Mughni, Muhammad Syafiq (Journal Of Human And Education (JAHE), 2025)
The task of teachers (ustadz/ ustadzah) in formal and non-formal education units is to carry out learning. In order for the implementation of learning to be effective and programmed, the teacher (ustadz/ ustadzah) must prepare a thorough learning plan. One of the learning plans prepared by the teacher (para asatidz) is at least a Learning Implementation Plan (RPP). There is a lack of understanding of the Learning Implementation Plan (RPP) for teachers (ustadz/ ustadzah), so that teachers (ustadz/ ustadzah) at Madrasah Diniyah SMP Islam Bustanul Hikmah never make a Learning Implementation Plan (RPP). As a solution, training and mentoring is provided with the aim of increasing teacher motivation, understanding and ability in preparing Learning Implementation Plans (RPP). The results of this activity show that 100% of the ustadz and ustadzah's motivation was very good in participating in the training and mentoring activities in preparing the Learning Implementation Plan (RPP), 77.78% of the ustadz and ustadzah understood the training and mentoring material, and 66.67% of the ustadz and ustadzah were able to prepare the plan. Learning Implementation (RPP). The results of this community service activity show good results and help ustadz and ustadzah in preparing Learning Implementation Plans (RPP) as guidelines and signs for implementing programmed and effective learning.